Continual improvement in outcome-based education (OBE) for industrial practicum training program / Sariwati Mohd Shariff , Shatina Saad - Mohd Shariff, Sariwati; Saad, Shatina (Institute of Business Excellence, 2010)
This paper aims to share the findings and continual improvements made to the curricular structure on industrial practicum training program in the Faculty of Business Management of a local public university based on a study carried out in 2005 - 2006. A total of 103 practicum students (25%) responded to a quantitative survey using a 5-point Likert scale to determine the practicum training effectiveness; followed by in-depth interviews on twelve purposive-selected trainees. Findings showed that the factors that make the industrial practicum training effective were: host organizations, roles of facilitators, roles of trainees and the training-learning curriculum in the practicum. The scope of study encompassed final semester business management students who had completed practicum attachments in various industries from multinational companies, national and local small-medium enterprises. The practical implications of this study resulted in a change of curriculum structure for practicum programs, improved administration and practicum evaluations on the students, and enhanced the universityindustrial linkages.